Hubungan Motivasi dan Supervisi Dengan Pendokumentasian Keperawatan - Dewi, Mursidah; Yellyanda, Yellyanda; Ernawati, Ernawati; Haryanti, Yan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the relationship between motivation and supervision with nursing documentation at the Rimbo Bujang Inpatient Health Center, Tebo Regency. This research method was cross sectional involving 52 nurses who worked in the inpatient care at the Rimbo Bujang Community Health Center, Tebo Regency. The statistical test used is chi square. The research results showed that 55.8% of nurses had high motivation, 55.8% carried out good supervision, 51.9% of nurses carried out incomplete nursing documentation. The Chi-Square statistical test obtained a significant value of p = 0.001 < 0.05, indicating that there was a relationship between motivation and nursing documentation. The supervision statistical test obtained a significant value of 0.000 (p < 0.05). There was a relationship between supervision and nursing documentation. The conclusion of the research is that there is a relationship between motivation and nurse supervision in carrying out nursing documentation at the Inpatient Hospital of Rimbo Bujang Community Health Center, Tebo Regency Keywords: Nursing Documentation, Motivation, Supervision